AD, Volume 5, n° 1, 1980 - Full Issue (Africa Development, 1980)
CONTENTS The Sahel Region HECTOR GAMBAROTTA ..................... 6 Transfert de Connaissances en Afrique : Histoire et Enseignements pour le Futur V. ALTARELLI HERZOG .................... 39 The Crisis in Planning : What Lessons for Nigeria? ANYAEGBUNAM W. OBI .................... 66 NIGERIA: Class Struggle and Foreign Policy: 1960- 78 AARON T. GANA ............................ 196